What are startup studios and how do they create value? A multiple case study investigation of startup studios through their business models - Mortleman, Juliet Mary (2022)
Distinct from startup supports such as accelerators, incubators, and venture capitalists. Startup studios (studios) represent a form of organisational co-founder to the startups they create and support. Studios take a portfolio approach to ideating, creating, and growing high-growth startups, employing a high level of systemisation. As studio numbers accelerate, their prominence and legitimacy are rising in entrepreneurial ecosystems. Furthermore, industry data demonstrates substantial performance potential. However, studios have lacked academic attention, and as entrepreneurs, corporates, universities, and governments increasingly look to the model to explore and exploit opportunities there is a need for greater clarity as to what studios are and how they create and capture value.